Порівняльна характеристика об’єму вживання в публіцистичному, художньому та науковому стилях на семантичному рівні - Данилович, Оксана Дмитрівна (My University, 2025)
The article is dedicated to the investigation of a comparative characteristic of usage volume on the semantic level in the publicistic, scientific and belle-lettres styles. The goal is to study and compare usage volume of lexical-semantic groups (LSG) of adjectives with LSG of nouns in 3 styles. The object of the study is usage volume on the semantic level. The comparison of usage volume of LSG of adjectives in three styles distinguished peculiarities of the set of adjectives for every style due to the influence of the style factor. Volume also shows how widely every LSG of adjectives reveals itself if a quantitative set is limited or on the contrary volume reaches its maximum that is also caused due to the goals of the style. Volume reveals its qualitative peculiarities (the set of adjectives) as well as quantitative ones. The highest indices of volume were distinguished for the belle-lettres style that comprise 10 LSG of adjectives “Estimation of the object in comparison with signs of others”, “Colour”, “Emotional state, feelings”, “Behaviour and actions to the object”, ”Composition and material”, “Natural and physical state”, “Traits of character, habits”, ”Speed”, “Appearance”, “Temperature”, “Estimation of mental abilities of a man”, ”Estimation of functional activity of organs and parts of the body”, the publicistic style contains 7 LSG of adjectives relating usage volume: “Field of activity”, “Age, time”, “Nationality”, “Estimation of the object by form, volume, size”, “Administrative, regional, class distinctions”, “Geographical position”, “Estimation of the object by space, distance, duration” and for the scientific style only one group of LSG of adjectives “Estimation of value, meaning, quality and function” was determined. The belle-lettres style presents itself as a wider system of the language which has the biggest number of LSG of adjectives with the highest indices of volumes. Hence it has a richer, colourful language that shows uniqueness, treasure of the language caused first of all by the tasks and functions of the belle-lettres style. A wider range of choice is determined in the publicistic style which reflects functioning those language means which are necessary for achieving goals of the publicistic style. The scientific style is characterized by the highest index of vocabulary selection prevailing mainly with a medium volume of filling of LSG of adjectives. Vocabulary of the scientific style is distinguished by conciseness, exactness, lack of expression. Key words: usage volume, adjective, noun, lexical-semantic group, style.
Keywords: об’єм вживання, прикметник, іменник, лексико-семантична група, стиль.